Analysis of chip quality and value at Norske Skog Pisa Mill, Brazil - Färlin, Agneta (2008)
Norske Skog's pulp and paper mill in Pisa, Brazil, was purchased by Norske Skog in 2000. Norske Skog is a world-leading producer of newsprint and magazine paper, with 18 paper mills around the world.